Physiotherapy Interventions in Diseases Idiopathic Pulmonary Fibrosis: Literature Review - Arisanti, Ni Kadek Dian; Antara, I Made Surya Widi; Prasetyo, Arsya Hayyu; Dewi, Rani Nafisa; Prasana, I Gede Eka Juli; Jeviana, Ariezta (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Idiopathic Pulmonary Fibrosis (IPF) is a chronic lung disease that causes lung tissue to stiffen and progressively decreases respiratory function. Patients often experience shortness of breath, fatigue, and decreased capacity for daily activities, which impacts their quality of life. While there is no cure for IPF, physiotherapy plays an important role in helping to manage symptoms and maintain lung function. Various interventions such as physical exercise, breathing techniques and pulmonary rehabilitation have been shown to improve patients' condition. Therefore, this study is needed to understand the effectiveness of physiotherapy interventions in supporting more optimal management of IPF. To assess the effectiveness of physiotherapy interventions such as physical exercise and breathing techniques in improving lung function and quality of life of IPF patients. Methods: Literature review was conducted by searching articles through Google Scholar, PEDro, PubMed, and Scopus databases using keywords related to IPF and physiotherapy interventions. Selection was done using inclusion-exclusion criteria with the help of PRISMA diagram. Results: Interventions such as aerobic exercise, strength training, breathing techniques (including pursed-lip breathing and diaphragmatic breathing), and pulmonary rehabilitation were shown to be effective in increasing functional capacity, reducing dyspnea, and improving the quality of life of IPF patients. Conclusion: Physiotherapy interventions effectively improve functional capacity, reduce symptoms, and enhance quality of life in idiopathic pulmonary fibrosis patients.